Conceptualisation of Lahore in Akhtar’s Lahore, I Am Coming (2017): a corpus stylistic analysis - Umer, Hajra; Zahra, Tehseen (Penerbit Universiti Kebangsaan Malaysia, 2023)
Urban literature deals with the conceptualisation of a city as characterised in a literary work. In these writings, the city is contested as a social and conceptual challenge. The current study examined the conceptualisation of the city of Lahore in Akhtar’s poetic collection Lahore, I Am Coming from the perspective of urban imaginaries utilising a corpus stylistic approach. For this purpose, theorisations related to urban imaginaries based on Cinar and Bender’s concept of the collective imagination of a city and Shweta Sur’s notion of heterotopic urban spaces were utilised as the theoretical framework. Moreover, the current analysis utilised the corpus techniques of keyword-in-context (KWIC) and concordance analysis to analyse the occurrence of the word Lahore in the selected corpus. This was done in an attempt to trace the conceptualisation of Lahore in the selected text. The findings showed that the collective imagination of Lahore can be mapped around four different kinds of sub-themes i.e. culture, history, the city vibe, and heterotopias. Furthermore, the concordance analysis of KWIC showed that heterotopic sites within Lahore are connected with the urban ecosystem shedding light on environmental degradation and ecological imbalance. The study is particularly useful in highlighting the contemporary Pakistani urban settlements and their portrayal in Pakistani literature. Furthermore, it has provided a new dimension to the fields of urban ecology and ecocriticism by reflecting on ecological imbalance and environmental hazards which are very much connected with the urban landscape of Lahore.